PATHOLOGICAL STATE OF THE HEPATOBILIARY SYSTEM DEPENDING ON THE TYPE OF OBESITY IN CHILDREN - Turaeva, Дилафруз; Garifullina, Лиля (International Journal of Scientific Pediatrics, 2025)
The prevalence of non-alcoholic fatty liver disease is increasing as the obesity epidemic grows worldwide, and is diagnosed at an earlier age and is pathogenetically associated with lipid metabolism pathology. Material and methods: The study involved 96 children with exogenous-constitutional obesity, who were divided into 2 groups. Group 1 with a uniform type of obesity, group 2 with abdominal obesity, and 44 healthy children with normal body weight. Lipid metabolism and liver ultrasound were studied. Results: Non-alcoholic fatty liver disease was observed in 50.0% of obese children, which occurred in 65.9% of children with visceral obesity. Non-alcoholic fatty liver disease is more common in children aged 16–18 with abdominal obesity (100%). It was found that steatosis develops earlier in obese boys than in girls and occurs against the background of clearly expressed lipid metabolism disorders. In non-alcoholic fatty liver disease, structural changes in the liver parenchyma are characterized by the simultaneous development of diffuse-focal processes, such as fatty degeneration and steatohepatitis against the background of unchanged parenchyma. Conclusion. Children with various types of obesity require comprehensive diagnostic, therapeutic and preventive measures to promptly identify disorders and reduce the risk of developing metabolic and inflammatory diseases of the hepatobiliary system and hormonal and metabolic disorders.